2015
DOI: 10.1002/chem.201500373
|View full text |Cite
|
Sign up to set email alerts
|

Crown‐Shaped Tungstogermanates as Solvent‐Controlled Dual Systems in the Formation of Vesicle‐Like Assemblies

Abstract: Reaction of early lanthanides, GeO2 , and Na2 WO4 in a NaOAc buffer results in large crown-shaped polyoxometalates based on [Ln2 GeW10 O38 ](6-) subunits. By using Ni(2+) as a crystallizing agent, [Na⊂Ln12 Ge6 W60 O228 (H2 O)24 ](35-) (Na⊂Ln12 ) hexamers formed by alternating β(1,5)/β(1,8) subunits were obtained for Ln=Pr, Nd. The addition of K(+) led to a similar anion for Ln=Sm, namely, [K⊂Sm12 Ge6 W60 O228 (H2 O)22 ](35-) (K⊂Sm12 ) and [K⊂K7 Ln24 Ge12 W120 O444 (OH)12 (H2 O)64 ](52-) (K⊂Ln24 ) dodecamers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Previous research demonstrates that emission colors of Ln-AMTs can be tuned through switching variable excitation lights, which can realize the emission-tunable property. , In addition, W–O–Ln bond angles near 150° will result in dπ–pπ–fπ orbital mixing, which can lead to inactivity of ET from AMT segments to Ln 3+ ions. Fortunately, no W–O–Ln bond angles near 150° in 1–3 have been found, which suggests that ET cannot be inhibited by dπ–pπ–fπ orbital mixing. In this work, excitation and emission spectra, decay lifetime curves, and time-resolved emission spectra (TRES) as measurement methods have been measured to analyze the PL properties of 1–3 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous research demonstrates that emission colors of Ln-AMTs can be tuned through switching variable excitation lights, which can realize the emission-tunable property. , In addition, W–O–Ln bond angles near 150° will result in dπ–pπ–fπ orbital mixing, which can lead to inactivity of ET from AMT segments to Ln 3+ ions. Fortunately, no W–O–Ln bond angles near 150° in 1–3 have been found, which suggests that ET cannot be inhibited by dπ–pπ–fπ orbital mixing. In this work, excitation and emission spectra, decay lifetime curves, and time-resolved emission spectra (TRES) as measurement methods have been measured to analyze the PL properties of 1–3 .…”
Section: Resultsmentioning
confidence: 99%
“…Several examples of polyanions comprising dilacunary β‐Keggin units are known 6a. d, g, 10 Interestingly, the Ce 20 ‐containing 100‐tungsto‐10‐germanate contains the same dilacunary {β(4,11)‐GeW 10 } Keggin fragments as Eu 12 6a. Reinoso et al.…”
Section: Resultsmentioning
confidence: 99%
“…showed that {GeW 10 } fragments can also be formed in situ by direct reaction of Na 2 WO 4 , GeO 2 , and lanthanide sources in acetate buffer 6d. g, 10j…”
Section: Resultsmentioning
confidence: 99%
“…To systematically explore the reactivity of Krebs-type M 2 anions (M = Mn, Co, Ni, Zn) toward 4f metals,w ef irst selected the salt Na 10 [Co 2 ]a sarepresentative precursor and reacted it with the whole series of Ln ions (1:1 ratio) in hot NaOAc buffer (Method1). The reactivity differed considerably along the Ln series, as observed for other Ln/POMs ynthetic systems [14] (Scheme 1). Although attempts with late 4f metals (Tb to Lu) only affordedt he pristine Co 2 precursor back, crystalline batches obtained from larger early-to-mid Ln ions (La to Gd) contained an additional side product with as ubstantially different framework (Ln 3 Co 2 ), as inferred unequivocally from the IR spectra (see Figure S1 in the Supporting Information for acomparisono ft he spectra with that of Co 2 among other building blocks).…”
Section: Synthetic Aspectsmentioning
confidence: 71%